Psychometric Properties of the Chinese Shortened Version of the Zuckerman–Kuhlman Personality Questionnaire in a Sample of Adolescents and Young Adults - Wang, Daoyang; Hu, Mingming; Zheng, Chanjin; Liu, Zhengguang (Frontiers in Psychology, 2017)
Introduction: The original 89-item Zuckerman-Kuhlman Personality Questionnaire (form III Revised, ZKPQ-III-R) is a widely accepted and used self-report measure for personality traits. This study assessed the reliability and construct validity of the Chinese short 46-item version of the ZKPQ-III-R in a sample of adolescents and young adults. Methodology: A total of 1,019 Chinese adolescents and young adults completed the Chinese version of the original 89-item version ZKPQ-III-R and short 46-item version ZKPQ-III-R, self-report measures of depression, life satisfaction, and subjective health complaints, the Big Five personality traits, and a substance use risk profile. We explored the internal consistency of five dimensions of the short 46-item version ZKPQ-III-R and compared it with observations in previous studies of Chinese and other populations. The structure of the questionnaire was analyzed by confirmatory factor analysis and exploratory structural equation modeling. Results: The short 46-item version ZKPQ-III-R had adequate internal consistency reliability for all five dimensions, with Cronbach α coefficients of 0.63 to 0.84. The concurrent validity of the short 46-item version ZKPQ-III-R was supported by significant correlations with depression, life satisfaction, and subjective health complaints. The short 46-item version ZKPQ-III-R had better fit, similar reliability coefficients, and slightly better construct and convergent validity than the 89-item version. Conclusion: The Chinese version of the 46-item ZKPQ-III-R support was found for reliability and validity of the measure of personality in Chinese adolescents and young adults.